Myanmar's terrestrial ecosystems: Status, threats and conservation opportunities. (December 2020) - Murray, Nicholas J.; Keith, David A.; Duncan, Adam; Tizard, Robert; Ferrer-Paris, Jose R.; Worthington, Thomas A.; Armstrong, Kate; Nyan Hlaing,; Win Thuya Htut,; Aung Htat Oo,; Kyaw Zay Ya,; Grantham, Hedley
Abstract: Myanmar is highly biodiverse, with more than 16, 000 plant, 314 mammal, 1131 bird, 293 reptile, and 139 amphibian species. Supporting this biodiversity is a variety of natural ecosystems—mostly undescribed—including tropical and subtropical forests, savannas, seasonally inundated wetlands, extensive shoreline and tidal systems, and alpine ecosystems. Although Myanmar contains some of the largest intact natural ecosystems in Southeast Asia, remaining ecosystems are under threat from accelerating land use intensification and over-exploitation. In this period of rapid change, a systematic risk assessment is urgently needed to estimate the extent and magnitude of human impacts and identify ecosystems most at risk to help guide strategic conservation action. Here we provide the first comprehensive conservation assessment of Myanmar's natural terrestrial ecosystems using the IUCN Red List of Ecosystems categories and criteria. We identified 64 ecosystem types for the assessment, and used models of ecosystem distributions and syntheses of existing data to estimate declines in distribution, range size, and functioning of each ecosystem. We found that more than a third (36.9%) of Myanmar's area has been converted to anthropogenic ecosystems over the last 2–3 centuries, leaving nearly half of Myanmar's ecosystems threatened (29 of 64 ecosystems). A quarter of Myanmar's ecosystems were identified as Data Deficient, reflecting a paucity of studies and an urgency for future research. Our results show that, with nearly two-thirds of Myanmar still covered in natural ecosystems, there is a crucial opportunity to develop a comprehensive protected area network that sufficiently represents Myanmar's terrestrial ecosystem diversity.